2018
DOI: 10.1080/21645515.2018.1509648
|View full text |Cite
|
Sign up to set email alerts
|

A phase III clinical trial to evaluate the safety and immunogenicity of 23-valent pneumococcal polysaccharide vaccine (PPV23) in healthy children, adults, and elderly

Abstract: To evaluate the safety and immunogenicity of a newly 23-valent pneumococcal polysaccharide vaccine (PPV23), a phase Ⅲ clinical trial was conducted in population aged ≥ 2 years. We conducted a randomized, double-blinded, active controlled trial, in which 1760 participants were randomly assigned in a 1:1 ratio to receive one dose of either the test vaccine or the control commercial vaccine. The surveillance period was 28 days. The 2-fold increase rate of anti-pneumococcal for 23 serotypes varied from 49.71% to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(36 reference statements)
0
8
1
Order By: Relevance
“…One study assessed immunogenicity of PPSV23 in COPD patients and healthy controls and found that there were no statistically significant differences in the antibody GMCs between COPD patients and healthy controls ( 9 ). The 2-fold increase rates of 23 serotypes in this study were not lower than those in the Phase III licensure clinical trial of PPSV23 conducted in China ( 10 ).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…One study assessed immunogenicity of PPSV23 in COPD patients and healthy controls and found that there were no statistically significant differences in the antibody GMCs between COPD patients and healthy controls ( 9 ). The 2-fold increase rates of 23 serotypes in this study were not lower than those in the Phase III licensure clinical trial of PPSV23 conducted in China ( 10 ).…”
Section: Discussioncontrasting
confidence: 67%
“…Finally, the study was short term and did not provide evidence of persistence of immunity. There are several studies reporting 1−2 years of immune persistence following PPSV23 vaccination of COPD patients (6)(7)9). Only one study reported long-term persistence (8).…”
Section: Discussionmentioning
confidence: 99%
“…As of August 8, 2023, more than 58 vaccines have been approved by WHO (Table 1), with more vaccines in clinical trials (Table 2). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] These vaccines are produced by various platforms, encompassing inactivated, protein subunit, mRNA, and adenovirus vector vaccines (Fig. 1).…”
Section: Current Covid-19 Preventive and Therapeutic Strategies Curre...mentioning
confidence: 99%
“…PCVs which have carrier protein conjugated to polysaccharide, induce B-cell memory response, and provide long-term immunity. 23valent PPV (PPSV23) showed robust immune response in adults >50 years and individuals 2-49 years having high risk or with chronic conditions (91,92). Efficacy of 13-valent PCV (PCV13) was observed among adults >65 years of age, in prevention of vaccine-type CAP and vaccine-type IPD which persisted till 4 years (96).…”
Section: Pneumococcal Vaccinesmentioning
confidence: 99%